2022
DOI: 10.1371/journal.pone.0270038
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices towards COVID-19 among college students in China: A systematic review and meta-analysis

Abstract: Background Since the outbreak of the respiratory infectious disease caused by the novel coronavirus in 2019, the COVID-19 epidemic has posed a serious threat to the life and safety of the public, and has also seriously affected the normal study and life of college students in China. Although a series of studies have been conducted on college students’ knowledge, attitudes and practices of COVID-19, the results vary widely. This study aimed to evaluate the pooled estimated level of knowledge, attitudes, and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…The current study showed that 95% of the participants had a good knowledge of COVID-19. This is consistent with the reports of similar studies that showed a good knowledge of COVID-19 among undergraduate students with about 85 -98% of undergraduate students interviewed having a good knowledge of COVID-19 causes, prevention and mode of transmission [15,[17][18][19]. This finding indicates that majority of the undergraduates sampled in the study had good knowledge and reliable sources on the information about COVID-19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study showed that 95% of the participants had a good knowledge of COVID-19. This is consistent with the reports of similar studies that showed a good knowledge of COVID-19 among undergraduate students with about 85 -98% of undergraduate students interviewed having a good knowledge of COVID-19 causes, prevention and mode of transmission [15,[17][18][19]. This finding indicates that majority of the undergraduates sampled in the study had good knowledge and reliable sources on the information about COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…All responses were collated, with the correct/appropriate response scored as "1" and wrong responses scored as "0". Knowledge of COVID-19 were graded as good (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and poor (≤15), while knowledge of COVID-19 vaccine was graded as good (6)(7)(8)(9)(10)(11), and poor (≤5). The attitude to COVID-19 vaccine were graded as good (4-6), and poor (≤3) also.…”
Section: Data Collectionmentioning
confidence: 99%
“…In order to grasp the status of university students' mental health research which has been a hot topic in the past 20 years, this paper uses the CSSCI source journal literature database as the data source and 'university students' mental health' as the search theme, during 2017-2021; the search results are shown in Table 1 [10][11][12]. Through comparative analysis, with the development of society, the mental health of college students has gradually received more attention, and it is worth noting that research on the new crown epidemic is focused on epidemiological and clinical studies [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Statistics of literature on the topic of 'mental health of college students' from 2017 to 2021 [19][20][21][22][23][24] Year Literature (number of articles) 2017 564 2018 789 2019 943 2020 1031 2021 2347…”
Section: Introductionmentioning
confidence: 99%
“…In two systematic reviews analyzing COVID-19 and the mental health of medical students, it was pointed out that the symptoms of depression, anxiety, and stress can be regarded as problematic to the examined cohorts of future physicians and that research is needed to ensure that they have adequate tools needed to provide high quality and empathetic care to future patients [8,9].…”
Section: Introductionmentioning
confidence: 99%